BLOCKCHAIN TECHNOLOGY FOR SECURE TRANSACTIONS: EVALUATING ITS POTENTIAL IN CYBER SECURITY - UmmeSania (PT. Radja Intercontinental Publishing, 2024)
Blockchain technology has garnered significant attention in recent years due to its potential to revolutionize secure transactions across various sectors. This paper investigates the potential of blockchain technology in bolstering cyber security, particularly in ensuring secure transactions in digital environments. Through a comprehensive review of existing literature and real-world case studies, this paper evaluates the effectiveness of blockchain in addressing cyber security challenges such as data tampering, identity theft, and transactional transparency. Furthermore, it discusses potential challenges and future research directions in leveraging blockchain for cybersecurity purposes.